DELIVERING AND COMMUNICATING THE VALUE OF BUSINESS FOR MSME IN TANGERANG - Larasati, Hasna; Rahmatika, Rizka Astari (Bina Nusantara University, 2023)
Strategies in maintaining a sustainable business along with changes in all factors such as changes in technology, market demand, economic conditions and other factors require MSMEs to carry out sustainable development to improve product or service quality so that they are able to compete with competitors. The condition of MSME competition which is relatively fast in following changes is a factor that influences the survival of MSME. In facing competition, MSMEs have strengths and opportunities along with facing weaknesses, challenges and obstacles that become limitations for MSMEs. The limitations faced by MSMEs have different levels of difficulty from each area where the business is carried out. One of the MSME communities in Tangerang has difficulty delivering and communicating business value or the advantages of its products and services. Factors that cause difficulty or failure for MSMEs are the lack of ability to communicate business value, lack of knowledge or basic communication, as well as the ability of MSMEs to carry out digitalization developments in their business. This study explains how to develop a communication strategy for MSMEs in delivering their advantages business value. The method used in this research is descriptive qualitative through interviews and observation. The result of this research is to provide education through socializations and workshops for MSMEs to be able to improve the quality of their communication in delivering business value through an effective communication strategy.